Pharmacists’ Research Contributions in the Fight against HIV/AIDs - Alexis E. Horace (AIDS Research and Treatment)
Pharmacists have made many contributions to HIV/AIDs research and are still showing their significance as members of the healthcare team through innovative clinical trials. Pharmacists are showing advances in several healthcare settings including inpatient, outpatient, and community pharmacies. Because of the complex regimens of highly active antiretroviral therapy (HAART), the increased life span of patients living with HIV, and other concomitant medications taken for comorbid disease states, there is a high risk for health-related complications and the development of adverse events. These adverse events may lead to decreased adherence to HAART, which may cause the development of HIV drug resistance. Pharmacists are providing examples through growing research on how they help combat medication-related errors and also continue to contribute as healthcare providers as a part of a holistic healthcare team.